Trauma talks an analysis of violence against women discourses in Toni Talks - Dionisio, Hanna Mhel M.
This study analyzes select episodes from a popular YouTube-based program, Toni Talks, which features victims of violence against women (VAW) who disclosed their traumatic experiences and voiced out their gendered realities. To shed light on how it contributes to the VAW discourse in the Philippines, critical discourse analysis (CDA) is used to deconstruct various multimodal discursive elements of each chosen episode to identify VAW-related messages, themes, and patterns. A radical feminist lens was then used to critique the emergent VAW-related discourses within the selected Toni Talks episodes. The study revealed that patriarchal ideologies and conservative beliefs influence the VAW discourses in Toni Talks, framing VAW victims as inspirational and forgiving sexual gatekeepers. While the program allows women to narrate their own stories, the overall representation of VAW discourse in Toni Talks furthers gender stereotypes and victim blaming culture.